THE ROLE OF ORGANIZATIONAL COMMUNICATION TO HANDLE CONFLICT: (Case study of Mixed-Use Building in the Engineering Department at The Rich Jogja Hotel and Jogja City Mall) - Ningrum, Dyaloka Puspita; Husen Mussahada, Muhamad; Syakdiah, Syakdiah (POPULIKA, 2024)
The Rich Jogja Hotel and Jogja City Mall are subsidiaries of PT. Garuda Mitra Sejati (GMS). This hotel and mall are unique because they carry the concept of a mixed-use building, which turned out to cause many problems, including (1) electricity, (2) evacuation routes, and (3) plumbing. This research uses a qualitative case study method to determine the role of organizational communication in handling conflict in engineering departments at The Rich Jogja Hotel and Jogja City Mall through concepts of mixed-use buildings. The research results show that intensive communication has been carried out by the hotel, mall, and holding teams, such as organizing open forums or sharing sessions with employees. Even in handling problems, company leaders still do not involve all parties, but only those relevant to the conflict. Keywords: Organizational Communication; Conflict; The Rich Jogja Hotel and Jogja City Mall.